Comparison of gastric emptying of a nondigestible capsule to a radio‐labelled meal in healthy and gastroparetic subjects - KUO, B.; McCALLUM, R. W.; KOCH, K. L.; SITRIN, M. D.; WO, J. M.; CHEY, W. D.; HASLER, W. L.; LACKNER, J. M.; KATZ, L. A.; SEMLER, J. R.; WILDING, G. E.; PARKMAN, H. P. (Alimentary pharmacology & therapeutics, 2008)
Summary Background  Gastric emptying scintigraphy (GES) using a radio‐labelled meal is used to measure gastric emptying. A nondigestible capsule, SmartPill, records luminal pH, temperature, and pressure during gastrointestinal transit providing a measure of gastric emptying time (GET). Aims  To compare gastric emptying time and GES by assessing their correlation, and to compare GET and GES for discriminating healthy subjects from gastroparetics. Methods  Eighty‐seven healthy subjects and 61 gastroparetics enrolled with simultaneous SmartPill and GES. Fasted subjects were ingested capsule and [99mTc]‐SC radio‐labelled meal. Images were obtained every 30 min for 6 h. Gastric emptying time and percentage of meal remaining at 2/4 h were determined for each subject. The sensitivity/specificity and receiver operating characteristic analysis of each measure were determined for each subject. Results  Correlation between GET and GES‐4 h was 0.73 and GES‐2 h was 0.63. The diagnostic accuracy from the receiver operating characteristic curve between gastroparetics and healthy subjects was GET = 0.83, GES‐4 h = 0.82 and GES‐2 h = 0.79. The 300‐min cut‐off time for GET gives sensitivity of 0.65 and specificity of 0.87 for diagnosis of gastroparesis. The corresponding sensitivity/specificity for 2 and 4 h standard GES measures were 0.34/0.93 and 0.44/0.93, respectively. Conclusion  SmartPill GET correlates with GES and discriminates between healthy and gastroparetic subjects offering a nonradioactive, standardized, ambulatory alternative to scintigraphy.